Rice Ecosystems in Hill Agriculture: Effect on Soil Biological Pools of Carbon, Nitrogen and Phosphorus - and D. Elad Daka Biam, Christy B.K. Sangma, Dwipendra Thakuria (Journal of the Indian Society of Soil Science, 2017)
This study characterized the slope, terrace (young and mature), and lowland hill rice ecosystems in terms of biological pools of carbon (C), nitrogen (N) and phosphorus (P). The biological pools like soil microbial biomass C, N and P (MBC, MBN and MBP), soil organic C (SOC), dissolved organic C (DOC), extractable organic N (EON), potentially mineralizable N (PMN), basal respiration (BAS), and the activity of dehydrogenase and phosphatase (DHA and PHA) varied significantly among rice ecosystem types and these pools were strongly influenced by the soil moisture gradient. Soils of lowland contained 33, 55 and 60% more SOC over that in soils of mature terrace, slope land and young terrace, respectively. The C:N:P ratio within microbial biomass ranged from 41:5:1 to 59:6:1 with the indication of narrow ratio in lowlands and stable terraces and wider ratio in slope land and young terrace. The Â mineralization potential of C, N and P is higher in the stabilized rice soils as compared to that in the disturbed rice soils. The C and N components of soils in lowland and stabilized upland terrace rice ecosystems seem to be self-sustained, but the major limiting factor was the availability of P. The rice ecosystems were significantly different from each other at 5% level of significance (as determined by Kruskal Wallis H Test incorporating Monte Carlo significance). The principal component analysis plot grouped rice fields according to rice ecosystem type with distinct soil moisture gradient, and such effects masked the impact of locational difference in biological pools. Overall, it can be concluded that moisture content in soils controls the size and dynamics of biological pools of C, N and P and the interrelationships among these parameters.